2022
DOI: 10.1519/ssc.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Lower-Body, Multijoint, Isometric and Dynamic Neuromuscular Assessment Variables With Snatch, and Clean and Jerk Performance in Competitive Weightlifters: A Meta-Analysis

Abstract: The purpose of this meta-analysis was to synthesize the literature and provide a robust estimate of the correlations between lower-body, multijoint, isometric and dynamic neuromuscular assessment variables and snatch (SN) and clean and jerk (C&J) performance in competitive weightlifters. A comprehensive search through 3 electronic databases (PubMed, SPORTDiscus, and Web of Science) returned 12 studies that met the inclusion criteria. Meta-analyses were performed on Pearson's correlations between SN and C&J per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that performance in the CMJ and the SJ were significantly correlated with weightlifting performance in both male and female weightlifters [6][7][8][9][10][11]13]. Additionally, a recent meta-analysis showed that performance in the CMJ and the SJ are the best predictors for weightlifting performance [14]. These strong correlations are derived from the biomechanical similarities, and mainly of the lower body triple extension (hip, knee, and ankle extensors), which may be observed in both weightlifting movements and vertical jumping attempts [8,19].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have shown that performance in the CMJ and the SJ were significantly correlated with weightlifting performance in both male and female weightlifters [6][7][8][9][10][11]13]. Additionally, a recent meta-analysis showed that performance in the CMJ and the SJ are the best predictors for weightlifting performance [14]. These strong correlations are derived from the biomechanical similarities, and mainly of the lower body triple extension (hip, knee, and ankle extensors), which may be observed in both weightlifting movements and vertical jumping attempts [8,19].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, lower correlations were found between the RSI and the clean and jerk, which might be attributed to the presence of the jerk in the movement pattern, masking perhaps a stronger correlation outcome. Although the 1-RM strength in the back squat and the front squat or/and in the power snatch and the power clean may be better predictors for competitive performance [14], coaches may consider using a simple, easily executed and practical field test, like the DJ, which provides an index of explosiveness (RSI, RSR) and is also a good predictor of weightlifting performance. However, these results should be viewed with caution since, according to the authors' knowledge, this is the first study that investigated the correlation between the RSI and the RSR with weightlifting performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations